Karakter Bentuk Hunian Suku Rejang Di Daerah Rawan Gempa (Studi Kasus: Desa Gunung Alam, Kabupaten Lebong) - Atik Prihatiningrum (Universitas Sebelas Maret Surakarta, 2020)
The knowledge of building housing by the Rejang clan in Gunung Alam Village by trial and error using local materials as well as a simple way of reflecting the uniqueness of the form of shelter in the Rejang clan community residing in mountainous rural areas. The focus of this research is to identify the relationship between the form of shelter and the realization of anticipation of occupancy as its role as adaptive shelter in earthquake prone areas. This research is a qualitative descriptive study describing the form of occupancy of the Rejang Clan by exploring the configuration of the building and its structural system to understand the form of occupancy of the Rejang Clan as an adaptive building in earthquake prone areas. The adaptability of the Rejang clan as a shelter in earthquake-prone areas has been implemented through the form of houses on stilts which have a ratio of widths and lengths of buildings 1: 2 with symmetrical and simple spatial arrangements. Ratio of balanced heights in each structure. However, the use of nails has been found in homes and the addition of space that forms a new mass behind the original mass of housing with brick material becomes a risk in the event of an earthquake in the future. Even so, the Rejang Clan occupancy in Gunung Alam Village is still strong to be inhabited by the Rejang Clan and is adaptive in responding to earthquake shocks.